Effects of short-term training on anthropometric, physical fitness and physiological variables of football players - Ghosh, K.; Bera, S. J.; Ghosh, S.; Singha, P.; Jana, A.; Mahapatra, M.; Khanna, G. L.; Manna, I. (Journal of Human Sport & Exercise, 2023)
Football is popular sports worldwide and required high level of physical fitness and physiological demand. Training may improve the physical fitness and physiological variables when given according to the principle of periodization. The present study was designed to investigate the effects of training on anthropometric, physical fitness and physiological variables of football players. Ninety five male football players (age 14-16 yrs.) were included, and twenty five were excluded, the remaining seventy were divided into control group (CG, n = 35) and experimental group (EG, n = 35). The volunteers of EG followed a training (2 hrs/d, 5 d/wk., for 6 wks.), no training was followed for CG. Assessments of anthropometric, physical fitness and physiological variables were performed at 0 week and after 6 weeks. Paired sample t-test was performed to find out the differences in selected variables. An increase (p < .05) in grip and back strength, flexibility, anaerobic power, VO2max, FEV1, FVC and PEFR; and reduction (p < .05) in body mass, BMI, percent body fat, fat mass, reaction time of hands, resting heart rate, systolic blood pressure, pulse pressure were noted among the volunteers of experimental group after 6 weeks of training. Training may improve the anthropometric, physical fitness and physiological variables of the football players, and thus improve performance.